A BIM-based decision-making framework for optimal seismic retrofit of existing buildings. (1st September 2021) - Caterino, Nicola; Nuzzo, Iolanda; Ianniello, Antonio; Varchetta, Giorgio; Cosenza, Edoardo
Abstract: The selection of the most suitable seismic retrofit strategy for an existing building may represent a challenging task, due to the multitude of technical solutions available, as well as to conflicting criteria involved in the decision-making process. Such an assessment encompasses several steps in which considerable data sets need to be gathered, stored, managed and exchanged between different project stakeholders, in order to provide a clear understanding of the as-built conditions along with the specific design options. In this context, Multi-Criteria Decision-Making (MCDM) methods represent a viable decision support system when different alternatives need to be evaluated according to a group of criteria, whereas the Building Information Modelling (BIM) methodology is a consolidated collaboration tool for data management and visualisation for construction projects. In this work, an integrated framework is proposed to increase the level of awareness of the Decision Maker (DM) in taking decisions exploiting the capabilities offered by BIM methodology integrated within a MCDM approach. First, the MCDM-BIM framework is presented and the potential benefits due to BIM in MCDM problems for seismic retrofit are highlighted. Then the idea is applied to a RC-frame building case study, modelled in a BIM environment. Three decision-making scenarios are simulated by considering different DM profiles and retrofit strategies. The alternative interventions are evaluated according to a set of criteria by employing data retrieved from the BIM model. Finally, the optimal solution is assessed for each decision-making scenario.